2014
DOI: 10.1080/02699931.2014.889661
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive mechanisms linking low trait positive affect to depressive symptoms: A prospective diary study

Abstract: Low trait positive affect represents an affective vulnerability to depression, but little research has examined mechanisms linking low trait positive affect to depressive symptoms. The current study investigated whether the cognitive strategies of dampening and positive rumination mediated the prospective association between low trait positive affect and depressive symptoms. Participants were 209 undergraduate students who participated in an eight-week online study. Depressive symptoms and trait temperament we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 23 publications
5
29
0
1
Order By: Relevance
“…Although it has been broadly recognized that high levels of NE indeed go hand in hand with depression (see Hyde et al 2008), we have now found further evidence suggesting that PE is also of great importance when we study depression in youth. More specifically, the finding that PE and depressive symptoms are negatively related is in agreement with a number of longitudinal studies on PE, showing that low PE is a risk factor for the development of depressive symptoms in youth (Verstraeten et al 2008;Harding et al 2014;Hudson et al 2015). Moreover, our data offer evidence supporting the assumption that NE and PE interact as this joint effect is significantly related to depressive symptoms in youth.…”
Section: Linking Temperamental Reactivity To Depressive Symptoms In Ysupporting
confidence: 91%
See 4 more Smart Citations
“…Although it has been broadly recognized that high levels of NE indeed go hand in hand with depression (see Hyde et al 2008), we have now found further evidence suggesting that PE is also of great importance when we study depression in youth. More specifically, the finding that PE and depressive symptoms are negatively related is in agreement with a number of longitudinal studies on PE, showing that low PE is a risk factor for the development of depressive symptoms in youth (Verstraeten et al 2008;Harding et al 2014;Hudson et al 2015). Moreover, our data offer evidence supporting the assumption that NE and PE interact as this joint effect is significantly related to depressive symptoms in youth.…”
Section: Linking Temperamental Reactivity To Depressive Symptoms In Ysupporting
confidence: 91%
“…Yet, in conforming with the results of Verstraeten et al (2012), no significant relationships were found in our study. This is in contrast with the findings of other studies that found that low PE was associated with maladaptive ruminative ER strategies (Verstraeten et al 2012) and less positive rumination (an adaptive ER strategy) (Harding et al 2014). There are several explanations for these null findings.…”
Section: Temperamental Reactivity and Er Strategiesmentioning
confidence: 60%
See 3 more Smart Citations